The Influence of Leadership Style, Gender, Compensation, and Development Career, Against Satisfaction Work at PT AXA Insurance Indonesia Employees - Markonah, Markonah; Zaky, Achmad (Dinasti Publisher, 2025)
This research aims to For Analyze The Influence of Leadership Style, Gender, Compensation, and Development Career, Against Satisfaction Work on Employees of PT AXA Insurance Indonesia. Research This use approach quantitative through distribution questionnaire The population in this study were all employees of PT Asuransi AXA totaling 300 employees, while the sample was taken using a sampling technique, namely Simple Random Sampling and obtained a sample of 50 people. The results of the study indicate that: Leadership style, Compensation and Career Development have a significant positive effect on employee job satisfaction, while Gender does not affect employee job satisfaction at PT Asuransi AXA. It is recommended that PT Asuransi AXA improve the goodness of leadership style, Compensation and Career Development so that employee job satisfaction at PT Asuransi AXA increases.